The Tax Policy and Tax Planning Approach to the Current Situation Analysis and Investigation - Zheng, Boya (Transactions on Economics, Business and Management Research, 2024)
Tax planning is also known as reasonable tax avoidance. Under the premise of paying taxes in accordance with the law and complying with the tax law, it is very reasonable to use appropriate means to avoid tax obligations and reduce the company's tax expenses. There is no lack of public figures who have low tax awareness so that tax evasion is penalized by tax regulators. Meanwhile, due to the introduction and official launch of the fourth phase of the Golden Tax, more tax evasion behaviors have been detected and penalized. While paying a large amount of back taxes, it also faces a ruined reputation as well as imprisonment. There is no lack of many individuals or enterprises do not pay attention to the national tax policy, the information is too closed, or even think it is the behavior of tax evasion and tax evasion, the decision-making is too cautious, and can not enjoy the tax relief policy. The purpose of this paper is to enhance the importance of tax planning for individuals and enterprises, and to better respond to the tax policy issued by the state.